Exploring the potential of coconut shell biomass for charcoal production - Kabir Ahmad, R. (Ain Shams University, 2022)
Coconut shells are produced in a vast amount around tropical countries that needs to be utilized properly. Thermochemical methods are the main route for converting biomass to charcoal. Percentage of some relative factors in the biomass such as low-density, low caloric value, high ash, SOX, NOX, moisture content, microstructure, and complex elements are its major drawbacks. Nevertheless, no scientific studies were conducted on the carbonization of converting coconut shells to charcoal from local to global scales. Therefore, comprehensive and precise data on its production is limited. To overcome these problems; biomass materials need to be evaluated to assure the suitability of the biomass for the thermochemical process to curtail the yearning of energy demand. For the overall efficiency of the biomass conversion processes into the preference biomass-derived fuel, it is important to understand the physicochemical characteristics of the biomass. The paper aims at understanding the specialties of coconut shell biomass, which is directly used for thermochemical conversion mainly for charcoal production via; chemical structure, energy potential, and morphological analysis. The biomass exhibits a high: density of 412 kg/m3, a calorific value of 19.4 MJ/kg, fixed carbon of 21.8, a volatile matter of 70.8, carbon of 40.1, and low amount moisture of 5.6, and ash of 1.8. EDX and XRF analysis revealed a low amount of complex heavy metals, trace amounts of sulfur, and nitrogen, thus pre-treatment is not required before its utilization, ideal for thermochemical conversion. The coconut shell possesses amorphous and crystalline carbonaceous materials based on the XRD spectrum. The morphology on FESEM images and surface area analysis shows that the coconut shell contains heterogeneous shapes and scales of macro-pores with high surface area and porosity in nature. These essential qualities are suitable for charcoal production, activated carbon, insect repellent, filler, incense sticks, and other applications. Coconut shell possesses remarkable properties such as carbon-rich and environmentally friendly solid fuel to other biomass and coal materials; hence, it is possible to produce alternative energy from coconut shell biomass due to its several characteristics. Â© 2021 THE AUTHORS